Adverse Childhood Experiences, Maternal/Fetal Attachment, and Maternal Mental Health - Jennifer Hinesley; Ananda Amstadter; Aradhana Sood; Robert A. Perera; Ronald Ramus; Susan Kornstein (Mary Ann Liebert, 2020)
Background: This pilot study investigated the potential impact of exposure to childhood adversity on variables known to be related to posttraumatic stress (including attachment, mental health, and perceived stress) in a clinic sample of pregnant women. Materials and Methods: Participants consisted of 101 pregnant women recruited from the Virginia Commonwealth University Health System in Richmond, VA. All participants completed the Adverse Childhood Experience (ACE) questionnaire, Parental Bonding Instrument, Maternal Fetal Attachment Scale, Posttraumatic Stress Disorder (PTSD) Checklist, Symptom Checklist, and the Perceived Stress Scale. Results: Increased exposure to ACEs was negatively associated with retrospective report of viewing one's mother and father as caring and involved. ACE exposure was a statistically significant predictor of viewing one's mother and father as intrusive and controlling. ACEs were positively associated with self-reported PTSD symptoms, depressive and anxious symptomatology, and perceived stress. No direct effect of adverse childhood events on maternal/fetal attachment was found. Conclusions: ACE associations are discussed in terms of study methodology and needs for future research. Providers may consider incorporating the ACE questionnaire to identify exposure to childhood adversity and events that may increase an individual's risk for toxic stress and negative health outcomes.